Analisis Kualitas Website E-Perpus Menggunakan Metode WebQual 4.0 dan Importance Performance Analysis (IPA) - Dhiannisa, Fina; Firliana, Rina; Wardani, Anita Sari (Universitas Methodist Indonesia, 2024)
The e-Perpus website is a digital library owned by SMA Negeri 4 Kediri. The e-Perpus website can only be used to view book availability and borrow books only. There is an assessment column for websites which are categorized into 3 criteria, namely good, adequate and poor. Based on these general criteria, it is difficult to know what aspects are considered good, sufficient, or poor. The aim of this research is to find out what indicators have or have not met user expectations for the website based on end user perceptions. This research uses the Webqual 4.0 method with 3 variables: usability quality, information quality, and service interaction quality and the Importance Performance Analysis (IPA) method to determine the level of performance and expectations for websites using a descriptive quantitative approach. Data collection was carried out by distributing questionnaires to 95 respondents and the results of the gap analysis showed that all indicators were negative, this indicates that the quality of the website has not met user expectations. The variable that has the biggest gap is the usability quality variable with an average of -0.60, then the service interaction quality variable with an average of -48, and finally the usability quality variable with an average of -0.36. The IPA results show that overall the indicators that require improvement are the ability to carry out tasks, relevant information and detailed information.